Позитивная социализация детей с интеллектуальной недостаточностью как необходимое условие их интеграции в обществе - Искакова, Г.К. (My University, 2013)
Integration into society of children with intellectual disabilities can be successful by increasing their domestic and social experience and communication content of special education with the surrounding reality.